Analysis of Publishing Medical Sciences Books with Phenomenological Approach - Zainab Sadat Noorbakhsh; Fatemeh Sheikhshoaei; Dariush Matlabi; Farzaneh Fazli (Tehran University of Medical Sciences, 2022)
Background and Aim: Medical resources are directly related to health of society and the book as one of the main sources has great importance. This study has been conducted to investigate pathology of medical sciences books publishing status and also identification of content, cultural and technical production challenges of these books in Iran from the viewpoint of publishers. Materials and Methods: The present study in terms of purpose, approach, and method is applicable, qualitative and phenomenology. The research tool has been semi - structured interview and community were publishers of medical sciences books in two sections academic (Five) and private (eight) publishers. The interviews continued until the data saturation stage (13 interviews). First, open and axial coding was performed, which finally extracted 402 codes and then was categorized into 74 categories, which were analyzed using qualitative content analysis. Results: The field of content production faced the most important challenges (53%), in which policy making absence (24 repetitions, 16%), no domestic high percentage of medical publication (23 repetitions, 16%), and the lack of expertise in medical publishers (11 repetitions, 7%), were declared by publishers. The problems of cultural production were in the second place with 39% and respectively include specialized and costly editing of the book, the lack of professional referees and the lack of structured review rules with 22 repetitions equivalent to 46%, 8 repetitions equivalent to 17% and 6 repetitions equivalent to 13%. The challenges of the technical production sector are reflected with a number equal to 8% of the total problems, which include the problems of raw materials printing and publishing (11 repetitions, 48%), lack of printing and publishing technology (5 repetitions, 23%) and the lack of technical expertise staff (3 repetitions, 13 percent). Conclusion: According to the findings of this study and the revealed funds of damages in the medical publishing industry, it can be concluded that many publishing challenges in Iran are rooted in general policies, rules and culture. Therefore, more serious attention to the professional field of medical publishing from the government and unbiased policy making in order to divert the concerns of publishers can solve many obstacles and difficulties.